Design of the Load Introduction of Continuous Fibre-Reinforced Components for Cyclic Loading - Deutschmann, Torben; Gadinger, Marc; Wartzack, Sandro; Krause, Dieter (Proceedings of the 35th Symposium Design for X (DFX2024), 2024)
The use of fibre-reinforced plastics (FRP) in structural components offers significant lightweight potential due to their high specific stiffness and strength. However, the complex fatigue behavior of FRP often leads to insufficient consideration of long-term strength during product development, which is typically compensated for by high safety factors. This study aims to explore additional lightweight potential by addressing fatigue phenomena more accurately, focusing on the critical area of load introduction. Bolted connections, commonly used for load introduction, are prone to bearing failure under cyclic loading. Therefore, a simplified design support for the load introduction in cyclically loaded FRP components is necessar
Keywords: Fibre-reinforced Plastics; Lightweight Design; Fatigue; Load Introduction